1995
DOI: 10.1523/jneurosci.15-01-00333.1995
|View full text |Cite
|
Sign up to set email alerts
|

Novel classes of responsive and unresponsive C nociceptors in human skin

Abstract: One hundred ninety-four cutaneous C-fibers were recorded from the human peroneal nerve; 118 units were found by mechanical stimuli and 76 units were detected by electrical stimulation through a surface electrode. Needle electrodes were then inserted for electrical intradermal stimulation in the innervation territory of the units. Afferent and efferent sympathetic C-fibers were identified by slowing of conduction velocity after activation either by physical or chemical skin stimuli, or by arousal maneuvers elic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
245
1
10

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 417 publications
(267 citation statements)
references
References 52 publications
11
245
1
10
Order By: Relevance
“…[11][12][13][14] The two may have different sensory/efferent pathways, and/or different sub-sets of nociceptors. 15,33 The difference in the flare and pain response to a heat-ramp stimulus among the normal and obese subjects may be indicative of such a dissociation and, in fact, would favor a concept that the organism attempts to elicit an early protective reaction (neurogenic vasodilatation) at a temperature (441C) just below that which will become injurious to tissue. 14 Flare can be suppressed or abolished by denervation, 21,42 local anesthetics, 12,21 capsaicin-desensitization, 22,34 disease (diabetes, post-herpetic neuralgia), 21,43 and aging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14] The two may have different sensory/efferent pathways, and/or different sub-sets of nociceptors. 15,33 The difference in the flare and pain response to a heat-ramp stimulus among the normal and obese subjects may be indicative of such a dissociation and, in fact, would favor a concept that the organism attempts to elicit an early protective reaction (neurogenic vasodilatation) at a temperature (441C) just below that which will become injurious to tissue. 14 Flare can be suppressed or abolished by denervation, 21,42 local anesthetics, 12,21 capsaicin-desensitization, 22,34 disease (diabetes, post-herpetic neuralgia), 21,43 and aging.…”
Section: Discussionmentioning
confidence: 99%
“…21,31,32 All four of these reactions, acute heat pain, pruritis, sensitization and flare reactions, are C-fiber mediated, apparently by utilizing different sub-sets of C-fibers. 15,33 Specific noxious and non-noxious stimuli are applied to the skin to activate nociceptive afferent neurons to induce a spreading hyperemia, which is visible as a neurogenic vasodilatory, or flare, response. 12,21,31,32,34 Assessment of the axon-reflex flare by noxious heat-and capsaicinstimulation and by non-noxious transcutaneous electrical stimulation can be used to measure C-fiber function.…”
Section: Introductionmentioning
confidence: 99%
“…A large variety of substances feed back onto nociceptors innervating the injured region and sensitize peripheral terminals by direct and indirect actions at ion channels, receptors, and second messenger cascades (87,102,111,112). The mechanisms by which inflammatory mediators recruit "silent" C-M i H i fibers by endowing these fibers with prolonged mechanical and heat sensitivity (25,60) is unknown but may involve long-lasting alterations in second messenger signaling cascades and sensitization of nocisensors. Decreased thermal and chemical thresholds in the primary area are due in part to sensitization of TRPV1 and TRPA1 by numerous components of the "inflammatory soup" including BK (36,(85)(86)(87)112).…”
Section: Adaptive and Maladaptive Shifts In Pain Thresholdmentioning
confidence: 99%
“…Heat nociceptor units are reported to be present in significant numbers in primate cutaneous nerves. Microneurography studies in the peroneal nerve of man have shown that 6% of C fibre afferents are heat nociceptor units (Schmidt, Schmelz, Forster, Ringkamp, Torebj ork & Handwerker, 1995). In monkey hairy skin it is reported that heat nociceptor afferents make up 7% of C fibres (Baumann, Simone, Shain & LaMotte, 1991), and in monkey glabrous skin they make up 5·5% of nociceptive C fibres (Georgopoulos, 1976).…”
Section: Species Differencesmentioning
confidence: 99%